Cumulative soccer heading amplifies the effects of brain activity observed during concurrent moderate exercise and continuous performance task in female youth soccer players. (March 2020) - Harriss, Alexandra; Johnson, Andrew M; Thompson, James W G; Walton, David M; Dickey, James P
Objectives: To determine whether youth female soccer players demonstrate spectral changes in electroencephalogram activity during a continuous performance test, related to cumulative soccer heading at rest and during exercise. Setting: Community soccer facilities. Participants: Twenty-four female youth soccer players (age: 13.1 ± 0.8 years, mass: 49.5 ± 8.6 kg, height: 1.6 ± 0.1 m). Methods: Players completed testing at four time points during the soccer season. The continuous performance test involved players responding to target stimuli or refraining from responding to non-target stimuli. Omission errors (player failed to respond to target stimuli) and commission errors (player responded to non-target stimuli) were assessed for each continuous performance test. Electroencephalogram frequency bandwidths were divided into Theta (4.0–7.9 Hz), Alpha1 (8.0–9.9 Hz), Alpha2 (10.0–12.9 Hz), Beta1 (13.0–17.9 Hz), and Beta2 (18.0–29.9 Hz). Linear mixed-effects modeling was performed on electroencephalogram power at electrode locations Fp1, Fp2, F3, F4, F7, F8, C3, and C4. Participants completed a continuous performance test during rest and moderate exercise. Results: Omission errors significantly increased during exercise compared to rest at all time points (p < 0.05), but not commission errors. Linear mixed-effects models revealed that there was a statistically significant increase in electroencephalogram power during exercise across all frequency bands (p < 0.05); the number of cumulative headers amplified this difference for Alpha1, Alpha2, and Beta2 (p < 0.05). There were no statistically significant differences between cumulative number of headers and remaining electroencephalogram frequency bands (all p values > 0.05). Conclusion: Moderate exercise may help to elicit sub-clinical changes in youth female soccer players due to cumulative head impacts, which are not apparent at rest.